2019
DOI: 10.1016/j.jhazmat.2019.03.064
|View full text |Cite
|
Sign up to set email alerts
|

An efficient mechanochemical synthesis of alpha-aluminum hydride: Synergistic effect of TiF3 on the crystallization rate and selective formation of alpha-aluminum hydride polymorph

Abstract: AlH 3 is one of the most promising hydrogen storage materials due to its high gravimetric hydrogen capacity and low dehydriding temperature. In present work, a convenient and cost-efficient solid-state mechanochemical reaction is proposed to obtain α-AlH 3 nano-composite. With the addition of TiF 3 , α-AlH 3 nano-composite was formed in a short period by milling of LiH and AlCl 3. Based on XRD and NMR results, the average grain size of the α-AlH 3 in the nano-composite was 45 nm. The reaction pathway as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(24 citation statements)
references
References 91 publications
(129 reference statements)
0
24
0
Order By: Relevance
“…A desired solution is to promote the redox activity and operate the redox materials at relatively low temperatures. Much research has been done to explore the promotion effects of the dopants on the performance of iron oxides [24] , using Pd [25] , Ti [26] , Zr [27] , Pt [28] , Ce [29] , and La [29] , amongst others [30] . The results revealed that precious metal additives could promote reduction reaction and diminished the re-oxidation temperature to 550 °C.…”
Section: Introductionmentioning
confidence: 99%
“…A desired solution is to promote the redox activity and operate the redox materials at relatively low temperatures. Much research has been done to explore the promotion effects of the dopants on the performance of iron oxides [24] , using Pd [25] , Ti [26] , Zr [27] , Pt [28] , Ce [29] , and La [29] , amongst others [30] . The results revealed that precious metal additives could promote reduction reaction and diminished the re-oxidation temperature to 550 °C.…”
Section: Introductionmentioning
confidence: 99%
“…characteristic peak for copper did not appear to change before or after the addition of NH 4 HCO 3 , according to the "Scherrer equation" (Duan et al, 2018(Duan et al, , 2019. Furthermore, the size of copper particles did not appear to change.…”
Section: Morphology and Structure Of The Porous Cathode Carbon Supportmentioning
confidence: 86%
“…[86] When ball milling the mixtures of LiH and AlCl 3 , the addition of TiF 3 will lead the reaction system to undergo several intermediate stages before the final product α-AlH 3 /LiCl is formed. [86] TiF 3 also significantly enhances the hydrogen desorption properties of AlH 3 [87] .…”
Section: Mechanochemical Synthesis By Ball Millingmentioning
confidence: 96%